Identification of the Casparian strip integrity factor (CIF) gene family in Brassica napus and functional prediction of mature CIF small peptides - Miao Cheng; Hanbing Hu; Rui Chen; Ling He; Shanshan Wang; Yuling Zheng; Jiten Yadav; Hosam O. Elansary; Nisha Jaswal; Deepak Bhanot; Changli Zeng; Xiaoyun Liu (BMC Plant Biology)
Abstract Background Small peptides of the CIF family act as signaling molecules and participate in important signaling pathways, playing crucial roles in the processes of plant development and the environmental response. However, the CIF family has not been identified in the allopolyploid Brassica napus. Results This study identified 16 BnCIFs coding genes in Brassica napus, classified into three phylogenetic subfamilies and four types (CIF1/2, CIF3, CIF4, TWS1) based on Arabidopsis thaliana homologs. Chromosomal distribution analysis revealed their even spread across 11 chromosomes, primarily inherited from Brassica rapa with evolutionary contributions from chromosomal segment duplication, recombination, and polyploidization. Conserved features were observed in mature BnCIFs peptides (21/23 amino acids), including an N-terminal DY motif, two central prolines, and hydrophilic C-terminal residues. Promoter regions contained multiple hormone- and stress-responsive cis-elements, suggesting roles in diverse regulatory processes. Spatiotemporal expression profiling demonstrated tissue-specific expression patterns within each BnCIF type, alongside broad responsiveness to exogenous hormones and abiotic stress, implying functional diversification. qRT-PCR analysis of CIF1/2-type genes under nitrogen treatments revealed significant upregulation in roots under low nitrogen, indicating potential involvement in nitrogen absorption/transport. Comparative structural analysis of GSO1/2 receptor kinases between Brassica napus and Arabidopsis thaliana suggested possible BnCIFs-GSO1/2 binding interactions. Conclusion Our study comprehensively identified BnCIFs in Brassica napus from aspects such as gene structure, phylogeny, chromosomal location, duplication and recombination, expression patterns, structural characteristics, conservation of mature small peptides after cleavage and processing, and their ability to bind to receptors. The results lay a foundation for further functional analysis of BnCIFs. In the further, deciphering the regulatory network of CIF genes may provide new targets for optimizing root architecture and breeding for stress resistance in Brassica napus.